Hepatitis B Virus Reactivation in Patients Receiving Chemotherapy and Immunosuppressive Therapy (Medico Legal Update, 2020)
Hepatitis B virus (HBV) infection is a serious and common infectious disease of the liver, affecting millionsof people throughout the world. The incubation period for HBV is 45-180 days, most commonly 60-90 days.Hepatitis B reactivation is the reappearance or rise of hepatitis B virus (HBV) DNA in the serum of patientswith past or chronic HBV infection. Reactivation can occur in a variety of clinical settings, usually in thecontext of an immunosuppressed state or immunosuppressive therapy. The aim of study is to find out thereasons that lead to reactivation of hepatitis B virus. The study conducted during the period from September2019 to February 2020 the sample size were 135 individuals include 85 patients and 50 control with 56.47%female and 43.53% male) blood samples. A 42 (49.41%) from patients have reactivated HBV positive resultsas detected by ELISA assay . A five samples at a rate of 5.88% from these are HBV reactivation by PCRtechnique.